2021
DOI: 10.3389/fmed.2020.594275
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: Pitfalls and Challenging Mimickers

Abstract: Sarcoidosis, a systemic granulomatous disease of unknown etiology, may mimic other conditions at presentation often resulting in delayed diagnosis. These conditions include infections, neoplasms, autoimmune, cardiovascular, and drug-induced diseases. This review highlights the most common sarcoidosis mimics that often lead to pitfalls in diagnosis and delay in appropriate treatment. Prior to invasive testing and initiating immunosuppressants (commonly corticosteroids), it is important to exclude sarcoid mimick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 202 publications
(35 reference statements)
1
17
0
1
Order By: Relevance
“…Few studies have reported on antiphospholipid syndrome and their findings differed with respect to the presence of antiphospholipid antibodies (38% vs. 2–5%) in sarcoidosis patients [ 1 , 2 , 3 , 8 , 13 , 31 , 32 , 33 ]. It has been reported in the literature that the presence of antiphospholipid antibodies in sarcoidosis patients is correlated with a poor prognosis [ 8 , 13 , 31 , 32 , 33 ], and some authors state that these antibodies are disease markers with a prolonged course and are associated with extrathoracic involvement and persistence of radiographic changes [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have reported on antiphospholipid syndrome and their findings differed with respect to the presence of antiphospholipid antibodies (38% vs. 2–5%) in sarcoidosis patients [ 1 , 2 , 3 , 8 , 13 , 31 , 32 , 33 ]. It has been reported in the literature that the presence of antiphospholipid antibodies in sarcoidosis patients is correlated with a poor prognosis [ 8 , 13 , 31 , 32 , 33 ], and some authors state that these antibodies are disease markers with a prolonged course and are associated with extrathoracic involvement and persistence of radiographic changes [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis is a frequently insidious, rare, multiorgan disease, and diagnosis is often a chance finding at a routine chest radiography, carried out for other reasons, typically observed in adolescents or young adults [ 1 , 2 ]. Lung involvement is common and symptoms may include cough, dyspnea and chest pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siblings and offspring of subjects suffering from S are five and four times more likely to develop the disease, respectively [ 75 , 76 , 77 , 78 ]. Different HLA second class (HLA-DR) alleles have been detected to be S-related [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ]: HLA DRB1*15 in the Turkish population [ 90 ]; HLADRB1*11 in subjects with extra-pulmonary S [ 91 ]; HLA DRB1*0401 in patients suffering from OS involvement [ 92 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to state, however, that both features may be absent. In such cases, a positive Interferon-gamma release assay (IGRA) or tuberculin skin test (TST) associated with a positive PCR on clinical specimens generally suggest the correct diagnosis [ 71 ]. Rarely (<1% of cases), sarcoidosis may mimic miliary TB, with diffuse micronodules randomly disseminated in both lungs [ 72 ].…”
Section: Differential Diagnosismentioning
confidence: 99%